2013
DOI: 10.1364/josaa.30.002225
|View full text |Cite
|
Sign up to set email alerts
|

Least-squares phase estimation with wrapped measurements and branch points

Abstract: A nonorthogonal model for 2D signals with rotational components is presented, which enables estimation of phase values from observations of its local gradients. In this research, the rotational components are caused by the presence of branch points, which indicates phase wrapping. Using the proposed model, the phase is estimated using standard least-squares or recently proposed wavelet techniques by processing a linear combination of the wrapped observed gradients and the curl generated by phase wrapping.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…TiO 2 is a widely studied support for metal particle catalysts because of various superior properties, such as photocatalytic ability, reducible oxidation state of surface Ti atoms, nontoxic and nonhazardous nature, abundant source, low price, high chemical stability, and so forth. As photocatalysts, the main drawbacks that hinder the practical application of TiO 2 are the low efficiency of visible-light utility due to their wide band gaps, the short lifetime of photo-induced carriers because of the fast electron–hole combination, and the low chemical reactivity of the surfaces. Loading transition-metal nanoclusters onto the TiO 2 substrate may enhance not only the catalytic activity of the transition-metal nanoclusters but also the photocatalytic performance of TiO 2 . It has been proved that loading of nickel clusters onto the TiO 2 surface can modulate the electronic structure and enhance the catalytic activity of the system notably.…”
Section: Introductionmentioning
confidence: 99%
“…TiO 2 is a widely studied support for metal particle catalysts because of various superior properties, such as photocatalytic ability, reducible oxidation state of surface Ti atoms, nontoxic and nonhazardous nature, abundant source, low price, high chemical stability, and so forth. As photocatalysts, the main drawbacks that hinder the practical application of TiO 2 are the low efficiency of visible-light utility due to their wide band gaps, the short lifetime of photo-induced carriers because of the fast electron–hole combination, and the low chemical reactivity of the surfaces. Loading transition-metal nanoclusters onto the TiO 2 substrate may enhance not only the catalytic activity of the transition-metal nanoclusters but also the photocatalytic performance of TiO 2 . It has been proved that loading of nickel clusters onto the TiO 2 surface can modulate the electronic structure and enhance the catalytic activity of the system notably.…”
Section: Introductionmentioning
confidence: 99%
“…Since the discovery by Allen et al (1992) that POAM can be easily created in the laboratory, it has been found in virtually every field of optics Yao & Padgett (2011);Tamburini et al (2012); Shalaev et al (2013); Kim et al (2013); Chen et al (2013) ;Cristi & Axtell (2013); Sun et al (2013); Ruane & Swatzlander (2013); Roux (2013); this ubiquity is evident in the more than 1000 papers citing the original work (Allen et al 1992). The demonstration that POAM is a natural consequence of the interaction of light and turbulence (Sanchez & Oesch 2011a,b;Oesch et al 2013), provides a mechanism by which POAM may be created in large quantities by astrophysical systems.…”
Section: Introductionmentioning
confidence: 99%